2019
DOI: 10.1037/xap0000196
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory focus and self-determination motives interact to predict students’ nutrition-habit intentions.

Abstract: Regulatory focus (Higgins, 1997) and self-determination (Deci & Ryan, 2000) are two motivation theories widely applied in health intervention research but never conjointly, despite sharing a number of theoretical similarities. In three studies (N = 578), we investigated how university students' self-determination motives to act upon their nutrition interact with induced regulatory focus and also regulatory message framing to predict their behaviour or intention to improve their eating habits. Results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
(121 reference statements)
4
9
0
Order By: Relevance
“…First, they confirm the interest of associating these two theoretical models in order to study a behavior. In this respect, they complement both the previous work of Lalot et al [14], who combined these two models to study nutrition habits, and the works of Vaughn [16] and Hui et al [15], who associated these two theoretical frameworks with another concept underlined by SDT (i.e., basic needs), in contexts other than health. Secondly, they improve understanding of the process through which health promotion focus is related with PA and thus complement the work of Laroche et al [10] showing a mediator in this relationship (i.e., SOC strategy).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…First, they confirm the interest of associating these two theoretical models in order to study a behavior. In this respect, they complement both the previous work of Lalot et al [14], who combined these two models to study nutrition habits, and the works of Vaughn [16] and Hui et al [15], who associated these two theoretical frameworks with another concept underlined by SDT (i.e., basic needs), in contexts other than health. Secondly, they improve understanding of the process through which health promotion focus is related with PA and thus complement the work of Laroche et al [10] showing a mediator in this relationship (i.e., SOC strategy).…”
Section: Discussionsupporting
confidence: 56%
“…To date, so far as we are aware, no research has examined the relationships between the six motivations underlined by SDT and the promotion and prevention foci. However, Lalot et al [14] have examined the interaction effects of intrinsic and extrinsic motives and message framing in terms of promotion versus prevention on the eating behaviors of students (i.e., personal intention to act, willingness to participate in an online program, interest for nutrition-related information). The authors showed that prevention focus framing worked best to promote nutrition behaviors for participants who reported higher extrinsic motives.…”
Section: Introductionmentioning
confidence: 99%
“…Our study corroborates earlier research on the impact of personality dispositions on various kinds of health behavior (e.g., Booth-Kewley and Vickers Jr 1994;Friedman 2000;Hampson et al 2006), as well as research more specifically focusing on the impact of motivational and affective dispositions on health information behavior (e.g., Gerend and Shepherd 2007;Hastall and Wagner 2017;Hevey and Dolan 2014;Lalot et al 2018;Sherman et al 2006). Therefore, with regard to clinical practice, our findings imply the necessity to anticipate divergent health information seeking behaviors and preferences between patients even when they are in the same situation (e.g., before cancer treatment; Eheman et al 2009).…”
Section: Discussionsupporting
confidence: 90%
“…These results conceptually replicate findings of earlier research on recalled everyday types of experiences ( Vaughn, 2017 , 2019 ; Kim et al, 2019 ; Vaughn et al, 2020 ) and experimental performance tasks ( Vaughn, 2017 ). Additionally, they complement the positive relationships research has found between promotion focus and autonomous, “want-to” motivation ( Lalot et al, 2018 ; Vaughn, 2018 ; Laroche et al, 2019 ).…”
Section: Discussionsupporting
confidence: 57%